Carbon footprint and greenhouse gas emissions of different rice-based cropping systems using LCA - Mohammad Mofizur Rahman Jahangir; Eduardo Aguilera; Jannatul Ferdous; Farah Mahjabin; Abdullah Al Asif; Moutakin Hossan; Hassan Ahmad; Maximilian Bauer; Alberto Sanz Cobeña; Christoph Müller; Mohammad Zaman (Scientific Reports)
Abstract There are many cropping systems on floodplain soils, but greenhouse gas (GHG) emission balances of these agricultural systems are rarely reported. Carbon (C) footprints of agricultural products were assessed using a co-designed life cycle assessment tool in major cropping systems in Bangladesh: rice-rice-rice (R-R-R/boro-aus-aman), rice-fallow-rice (R-F-R/boro-fallow-aman), maize-fallow-rice (M-F-R), wheat-mungbean-rice (W-Mu-R), and potato-rice-fallow (P-R-F) along with the field measurement of some of the systems. The rice system with dryland crops had higher nitrous oxide (N2O) emissions (3.8 in maize, 4.5 in potato and 0.92 kg N2O–N ha−1 in mungbean) than sole rice (0.73 in boro, 0.57 in aus and 1.94 kg N2O–N ha−1 in aman) systems but methane (CH4) emissions exhibited the opposite. Methane dominated, accounting for 50–80% of total emissions in rice systems. The boro rice-based systems (R-R-R and R-F-R) had the highest C footprint (ca. 25.8 and 19.2 Mg CO2e ha−1) while the P-F-R (12.3 Mg CO2e ha−1) and M-F-R (12.6 Mg CO2e ha−1) had the lowest C footprint. Boro and aus were more suitable to reduce C footprint. Measured CH4 and N2O data agreed well with the IPCC Tier 1 estimates but further study on GHG measurements in other agroecosystems and cropping systems are required to validate the estimation for adopting suitable GHG mitigation strategies.